Civil society and the family - Muddiman, Esther; Power, Sally; Taylor, Chris (Bristol : Policy Press, an imprint of Bristol University Press, 2020)
The relationship between the family and civil society has always been complex, with the family often regarded as separate from, or even oppositional to, civil society. Taking a fresh empirical approach, Muddiman, Power and Taylor reveal how such separation underestimates the important role the family plays in civil society. Considering the impact of family events, dinner table debates, intergenerational transmission of virtues and the role of the mother, this enlightening book draws on survey data from 1000 young people, a sample of their parents and grandparents, and extended family interviews, to uncover how civil engagement, activism and political participation are inherited and fostered within the home.
Title from publisher's bibliographic system (viewed on 19 Mar 2021).
Keywords: Civil society; Families